2015
DOI: 10.1242/bio.015206
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic microtubule organization and mitochondrial transport are regulated by distinct Kinesin-1 pathways

Abstract: The microtubule (MT) plus-end motor kinesin heavy chain (Khc) is well known for its role in long distance cargo transport. Recent evidence showed that Khc is also required for the organization of the cellular MT network by mediating MT sliding. We found that mutations in Khc and the gene of its adaptor protein, kinesin light chain (Klc) resulted in identical bristle morphology defects, with the upper part of the bristle being thinner and flatter than normal and failing to taper towards the bristle tip. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The affected residue corresponds to D1933 in human DYNC1H1, and is found in the loop between β-strand S2 and helix H2 in the luminalfacing potion of the AAA+ domain. In an MT-gliding assay using fully recombinant wild-type human dynein complex and mutant dynein complex (DYNC1H1 D/V ), we demonstrated that this mutation significantly reduced MT-gliding activity, similar to the reduction in bristle mitochondrial net velocity found in our previous study (Melkov et al, 2015). Thus, our genetic and biochemical characterization revealed that the protein encoded by Dhc64C 8-1 is a 'slow' dynein mutant.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The affected residue corresponds to D1933 in human DYNC1H1, and is found in the loop between β-strand S2 and helix H2 in the luminalfacing potion of the AAA+ domain. In an MT-gliding assay using fully recombinant wild-type human dynein complex and mutant dynein complex (DYNC1H1 D/V ), we demonstrated that this mutation significantly reduced MT-gliding activity, similar to the reduction in bristle mitochondrial net velocity found in our previous study (Melkov et al, 2015). Thus, our genetic and biochemical characterization revealed that the protein encoded by Dhc64C 8-1 is a 'slow' dynein mutant.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, our genetic and biochemical characterization revealed that the protein encoded by Dhc64C 8-1 is a 'slow' dynein mutant. The fact that this variant is a 'slow' dynein mutant, along with our finding that the net velocity of mitochondrial transport in both anterograde and retrograde directions is highly reduced in the presence of this allele (Melkov et al, 2015), provides further support for the notion that Dhc64C directly regulates anterograde and retrograde mitochondrial transport along the bristle shaft.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations